Systemowe i metodologiczne warunki poprawy efektywności projektowania inwestycji produkcyjnych - Szulc, Ryszard (Wydział Prawa i Administracji UAM, 1978)
The article contains an analysis of relationship between the economic system of designing offices and the methodology of appraising investment effectiveness, being in force since 1973. It contains also the appraisal of the impact of those relationships on the effectiveness of projecting investment tasks. As it results from the presented analysis, the dependence of the amount of incomes, of the incomes of designing units on the cost calculation value of projects is an anti-stimulus with respect to optimization of the utilization of investment resources at lower management levels. The discussed relationship obliges the designing units to search for such project solutions which will enable them to maximize investment outlays. The positive feature of the methodology in question is that it stimulates designing units to ensure the minimum, desirable from the social viewpoint, level of investment effectiveness due to the introduction of investment outlays and effects discount. Since various branches differ considerably as to the rate of technical progress implemented, requirements concerning the minimum level of investment effectiveness should, according to the author, be differentiated appropriately in relation to the real branch conditions. Such a solution would permit the allocation of investments on the basis of economic calculus made at the level of an industrial branch on the way of considering macro and microeconomic preferences. The last question dealt with in the article concerns the utilization of the calculus of investment effectiveness as a normative calculus for the operational sphere. The consequence of such a move should be routine monitoring of operational activities and the creation of possibilities for gathering the data necessary for improvements in designing production projects.
The System and Methodological Conditions of Effectiveness Improvements in Projecting Production Investments